ANALYTICAL AND NUMERICAL ASPECT OF COINCIDENCE POINT PROBLEM OF QUASI-CONTRACTIVE OPERATORS - Gursoy, Faik; Erturk, Muzeyyen; Khan, Abdul Rahim; Karakaya, Vatan (PUBLICATIONS L INSTITUT MATHEMATIQUE MATEMATICKI, 2019)
We propose a new Jungck-S iteration method for a class of quasi-contractive operators on a convex metric space and study its strong convergence, rate of convergence and stability. We also provide conditions under which convergence of this method is equivalent to Jungck-Ishikawa iteration method. Some numerical examples are provided to validate the theoretical findings obtained herein. Our results are refinement and extension of the corresponding ones existing in the current literature.
Keywords: Jungck type iteration methods; quasi-contractive operators; convergence; rate of convergence; stability; S-ITERATION PROCESS; FIXED-POINT; NONEXPANSIVE-MAPPINGS; Mathematics